A short literary history of the United States - Klarer, Mario, 1962- (New York : Routledge, 2014)
"A Short Literary History of the United States offers an introduction to American Literature for students wanting to acquaint themselves with the most important periods, authors and works of American literary history. Comprehensive yet concise, it provides an essential overview of the different currents in American literature in an accessible, engaging style. This book offers:Coverage from the pre-colonial era to the present, including new media formats Coverage of the evolution of literary traditions, themes, and aesthetics Historical background, visiting the origins of content and form Overviews and comparisons of individual authors Readings of individual texts, contextualized within American cultural history A list of secondary readings, a glossary and links to open-access versions of essential texts.This book is the ideal companion to primary sources for courses in American Literature, American Studies, and others, or as a study aid for exams"--
1. Discovery narratives -- 2. Colonial literature -- 3. Literature of the early republic -- 4. Transcendentalism -- 5. American Renaissance -- 6. Gilded age-- realism -- 7. Modernism -- 8. Postmodernism -- 9. Ethnic voices -- 10. Literary theory in the United States.
First published in 2013 by C.H. Beck.
Keywords: American literature -- History and criticism; Electronic books